(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Chakra are believed to be part of subtle body, thought to vitalize the physical and mental status of an individual. Muladhara, Swadhishtana, Manipura, Anahata, Vishuddha and Ajna are called Shadchakra. Ayurveda is based on Tridosha Sidhantha, in which Vata Dosha has prime control over all functions of body, renders Prana to livings. Functions and site of Vata Dosha and Shad Chakra are found to be identical in some constituents. The function of Chakra is to spin and draw in this universal life force energy to keep the spiritual, mental, emotional and physical health of the body in balance. Prana Vata is seen related with Ajna Chakra, Udana Vata with Vishuddha Chakra, Vyana Vata with Anahata Chakra, Samana Vata with Manipura Chakra, Apana Vata with Muladhara and Swadhishtana Chakra respectively. Vata Dosha prompts all types of actions, coordinates physical and mental activities, likewise Chakra modulate the flow of subtle energy. Movement of energy is vital to life and the energetic process in body is caused by nervous system. The autonomic and somatic nervous system is most relevant with action of Chakra dealing with involuntary and voluntary response of the body as per need.